Is the Interplay between Epigenetic Markers Related to the Acclimation of Cork Oak Plants to High Temperatures? - Correia, Barbara; Valledor, Luis; Meijón, Mónica; Rodriguez, José Luis; Dias, Maria Celeste; Santos, Conceição; Cañal, Maria Jesus; Rodriguez, Roberto; Pinto, Glória (PLoS ONE, 2013)
Trees necessarily experience changes in temperature, requiring efficient short-term strategies that become crucial in environmental change adaptability. DNA methylation and histone posttranslational modifications have been shown to play a key role in both epigenetic control and plant functional status under stress by controlling the functional state of chromatin and gene expression. Cork oak (Quercus suber L.) is a key stone of the Mediterranean region, growing at temperatures of 45°C. This species was subjected to a cumulative temperature increase from 25°C to 55°C under laboratory conditions in order to test the hypothesis that epigenetic code is related to heat stress tolerance. Electrolyte leakage increased after 35°C, but all plants survived to 55°C. DNA methylation and acetylated histone H3 (AcH3) levels were monitored by HPCE (high performance capillary electrophoresis), MS-RAPD (methylation-sensitive random-amplified polymorphic DNA) and Protein Gel Blot analysis and the spatial distribution of the modifications was assessed using a confocal microscope. DNA methylation analysed by HPCE revealed an increase at 55°C, while MS-RAPD results pointed to dynamic methylation-demethylation patterns over stress. Protein Gel Blot showed the abundance index of AcH3 decreasing from 25°C to 45°C. The immunohistochemical detection of 5-mC (5-methyl-2′-deoxycytidine) and AcH3 came upon the previous results. These results indicate that epigenetic mechanisms such as DNA methylation and histone H3 acetylation have opposite and particular dynamics that can be crucial for the stepwise establishment of this species into such high stress (55°C), allowing its acclimation and survival. This is the first report that assesses epigenetic regulation in order to investigate heat tolerance in forest trees.
The following values have no corresponding Zotero field: publisher: Public Library of Science accession-num: 23326451
Keywords: Acclimatization; Acclimatization: genetics; Acetylation; Blotting; CHROMATIN; CORK oak (citation; Deoxycytidine; Deoxycytidine: analogs & derivatives; Deoxycytidine: metabolism; DNA; DNA methylation; Electrolytes; Electrolytes: metabolism; Epigenesis; Gene expression; Genetic; Genetic Markers; Genome; Heat-Shock Response; Heat-Shock Response: genetics; Histones; Histones: metabolism; Physiological; Physiological: genetics; Plant; Plant Leaves; Plant Leaves: metabolism; Plant: genetics; POST-translational modification; Quercus; Quercus: genetics; Quercus: physiology; Random Amplified Polymorphic DNA Technique; Stress; tags); Temperature; TREES -- Research; Western

Isoscapes of tree-ring carbon-13 perform like meteorological networks in predicting regional precipitation patterns - del Castillo, Jorge; Aguilera, Monica; Voltas, Jordi; Pedro Ferrio, Juan (JOURNAL OF GEOPHYSICAL RESEARCH-BIOGEOSCIENCES, 2013)
Stable isotopes in tree rings provide climatic information with annual resolution dating back for centuries or even millennia. However, deriving spatially explicit climate models from isotope networks remains challenging. Here we propose a methodology to model regional precipitation from carbon isotope discrimination (Delta C-13) in tree rings by (1) building regional spatial models of Delta C-13 (isoscapes) and (2) deriving precipitation maps from Delta C-13-isoscapes, taking advantage of the response of Delta C-13 to precipitation in seasonally dry climates. As a case study, we modeled the spatial distribution of mean annual precipitation (MAP) in the northeastern Iberian Peninsula, a region with complex topography and climate (MAP = 303-1086 mm). We compiled wood Delta C-13 data for two Mediterranean species that exhibit complementary responses to seasonal precipitation (Pinus halepensis Mill., N = 38; Quercus ilex L.; N= 44; pooling period: 1975-2008). By combining multiple regression and geostatistical interpolation, we generated one Delta C-13-isoscape for each species. A spatial model of MAP was then built as the sum of two complementary maps of seasonal precipitation, each one derived from the corresponding Delta C-13-isoscape (September-November from Q. ilex; December-August from P. halepensis). Our approach showed a predictive power for MAP (RMSE = 84 mm) nearly identical to that obtained by interpolating data directly from a similarly dense network of meteorological stations (RMSE = 80-83 mm, N= 65), being only outperformed when using a much denser meteorological network (RMSE = 56-57 mm, N = 340). This method offers new avenues for modeling spatial variability of past precipitation, exploiting the large amount of information currently available from tree-ring networks.
CitationCitationThe following values have no corresponding Zotero field: pub-location: 2000 FLORIDA AVE NW, WASHINGTON, DC 20009 USA publisher: AMER GEOPHYSICAL UNION
Keywords: ARCHAEOBOTANICAL REMAINS; ATMOSPHERIC CO2; CARBON-ISOTOPE DISCRIMINATION; climate; DELTA-C-13; PINUS-HALEPENSIS; RAINFALL; STABLE-ISOTOPES; Temperature

Seasonal and inter-annual variability of bud development as related to climate in two coexisting Mediterranean Quercus species - Alla, Arben Q.; Camarero, J. Julio; Montserrat-Martí, Gabriel (Annals of Botany, 2013)
Background and Aims In trees, bud development is driven by endogenous and exogenous factors such as species and climate, respectively. However, knowledge is scarce on how these factors drive changes in bud size across different time scales.Methods The seasonal patterns of apical bud enlargement are related to primary and secondary growth in two coexisting Mediterranean oaks with contrasting leaf habit (Quercus ilex, evergreen; Quercus faginea, deciduous) over three years. In addition, the climatic factors driving changes in bud size of the two oak species were determined by correlating bud mass with climatic variables at different time scales (from 5 to 30 d) over a 15-year period.Key Results The maximum enlargement rate of buds was reached between late July and mid-August in both species. Moreover, apical bud size increased with minimum air temperatures during the period of maximum bud enlargement rates.Conclusions The forecasted rising minimum air temperatures predicted by climatic models may affect bud size and consequently alter crown architecture differentially in sympatric Mediterranean oaks. However, the involvement of several drivers controlling the final size of buds makes it difficult to predict the changes in bud size as related to ongoing climate warming.
10.1093/aob/mcs24710.1093/aob/mcs247
Keywords: Bud size; current-year stem; Quercus faginea; quercus ilex subsp. ballota; summer growth; Temperature

Why only some plants emit isoprene. - Monson, Russell K.; Jones, Ryan T.; Rosenstiel, Todd N.; Schnitzler, Jörg-Peter (Plant, cell & environment, 2012)
Isoprene (2-methyl-1,3-butadiene) is emitted from many plants and it appears to have an adaptive role in protecting leaves from abiotic stress. However, only some species emit isoprene. Isoprene emission has appeared and been lost many times independently during the evolution of plants. As an example, our phylogenetic analysis shows that isoprene emission is likely ancestral within the family Fabaceae (= Leguminosae), but that it has been lost at least 16 times and secondarily gained at least 10 times through independent evolutionary events. Within the division Pteridophyta (ferns), we conservatively estimate that isoprene emissions have been gained five times and lost two times through independent evolutionary events. Within the genus Quercus (oaks), isoprene emissions have been lost from one clade, but replaced by a novel type of light-dependent monoterpene emissions that uses the same metabolic pathways and substrates as isoprene emissions. This novel type of monoterpene emissions has appeared at least twice independently within Quercus, and has been lost from 9% of the individuals within a single population of Quercus suber. Gain and loss of gene function for isoprene synthase is possible through relatively few mutations. Thus, this trait appears frequently in lineages; but, once it appears, the time available for evolutionary radiation into environments that select for the trait is short relative to the time required for mutations capable of producing a non-functional isoprene synthase gene. The high frequency of gains and losses of the trait and its heterogeneous taxonomic distribution in plants may be explained by the relatively few mutations necessary to produce or lose the isoprene synthase gene combined with the assumption that isoprene emission is advantageous in a narrow range of environments and phenotypes.
The following values have no corresponding Zotero field: accession-num: 22998549
Keywords: Drought; ferns; phloem; phylogeny; substrate; Temperature; thermotolerance; ﬁtness

Scavenging in Mediterranean ecosystems: effect of the invasive Argentine ant - Angulo, Elena; Caut, Stéphane; Cerdá, Xim (Biological Invasions, 2011)
Above-ground invertebrates may represent a high proportion of animal biomass, but few data are available on their fate after death. In Mediterranean ant communities, they are frequently scavenged by ants. Here, we assessed the consequences of Argentine ant invasion on the removal of arthropod corpses in Don˜ana National Park (SW Spain). In three natural habitats that differed in their degree of vegetation cover (i.e. protection for ants against high temperatures), we experimentally provided dead Drosophila, and observed their disappearance over a 60-min period at different times of day and year. The habitats used were isolated cork oak trees, pine tree forest and dry scrubland; we compared invaded with uninvaded plots in each. Oak trees were the most invaded habitat, while scrubland was the least and the only one where the Argentine ant coexisted with native ant species. In accordance with this degree of invasion, the Argentine ant removed the highest percentage of dead ﬂies in oak trees and the lowest in scrubland. Its performance as scavenger was higher than uninvaded ant communities, but it was reduced at high temperatures, when native species were highly efﬁcient. The saturated distribution of the Argentine ant colony seems to be the key to its efﬁciency. We discuss how the occurrence and scavenger efﬁciency of the Argentine ant could affect the nutrient cycling and the progression of its invasion.
The following values have no corresponding Zotero field: publisher: Springer Netherlands
Keywords: á; Ant communities; Arthropod corpses; Doñana; Linepithema humile; linepithema humile á don; Temperature; temperature á ant communities

Mismatch between the timing of oviposition and the seasonal optimum. The stochastic phenology of Mediterranean acorn weevils - Bonal, Raul; Muñoz, Alberto; MARÍA ESPELTA, JOSEP (Ecological Entomology, 2010)
1. The timing of reproduction is predicted to match the period of maximum food availability. In this sense, the case of many phytophagous insects in temperate regions is very illustrative, as their larvae usually depend on a resource only available for a limited period of time each year. 2. For 3 years the interactions between the weevil Curculio elephas and the Mediterranean Holm oak Quercus ilex were studied. Weevil larvae grow within the acorns, feeding on the cotyledons. The timing of oviposition will determine food availability for the larvae, as acorns stop growing once they are attacked. 3. Acorn temporal growing patterns did not change between years and food availability for larvae was at its highest in October, when temperature was still suitable for larval development. However, oviposition phenology did change between years. In 2002 females oviposited later, larvae grew within larger acorns, and their body mass was significantly higher than in 2003 or 2004, when females oviposited into early acorns. 4. Thus, weevils do not always adjust oviposition to the best possible feeding conditions for their offspring. Rather, they seem to maximise their own lifetime fitness, ovipositing as soon as they emerge in late summer. Emergence, in turn, depends strongly on stochastic events such as summer storms in the Mediterranean region. 5. Under a climate change perspective, the trend towards higher August rainfall recorded in our study area may alter oviposition phenology, with the subsequent cascade effects on weevil body size and fitness
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn; adult emergence; Curculio; oviposition; Phenology; stochastic events; Temperature; timing of reproduction

Drought, warming and soil fertilization effects on leaf volatile terpene concentrations in Pinus halepensis and Quercus ilex - Blanch, Josep-salvador; Penuelas, Josep; Sardans, Jordi; Llusia, Joan (Acta Physiologiae Plantarum, 2008)
The changes in foliar concentrations of volatile terpenes in response to water stress, fertilization and temperature were analyzed in Pinus halepensis and Quercus ilex. The most abundant terpenes found in both species were a-pinene and D 3 -carene. b-Pinene and myrcene were also abundant in both species. P. halepensis concentrations were much greater than those of Q. ilex in agreement with the lack of storage in the latter species (15205.60 ± 1140.04 vs. 0.54 ± 0.08 lg g -1 [d.m.]). The drought treatment (reduction to 1/3 of full watering) signiﬁcantly increased the total terpene concentrations in both species (54% in P. halepensis and 119% in Q. ilex). The fertilization treatment (addition of either 250 kg N ha -1 or 250 kg P ha -1 or both) had no signiﬁcant effects on terpene foliar concentrations. The terpene concentrations increased from 0.25 lg g -1 [d.m.] at 30C to 0.70 lg g -1 [d.m.] at 40C in Q. ilex (the non-storing species) and from 2,240 lg g -1 [d.m.] at 30C to 15,621 lg g -1 [d.m.] at 40C in P. halepensis (the storing species). Both species presented negative relationship between terpene concentrations and relative water contents (RWC). The results of this study show that higher terpene concentrations can be expected in the warmer and drier conditions predicted for the next decades in the Mediterranean region.
Keywords: fertilization; Pinus halepensis; Quercus ilex; Temperature; terpene concentration; water stress

Responses of Photosynthetic and Defence Systems to High Temperature Stress in Quercus suber L Seedlings Grown under Elevated CO2 - FARIA, T.; Vaz, M.; Schwanz, P.; PolIe, A. (Plant biology (Stuttgart, Germany), 2008)
Growth in elevated CO2 led to an increase in biomass production per plant as a result of enhanced carbon uptake and lower rates of respiration, compared to ambient C02-grown plants. No down-regulation of photosynthesis was found after six months of growth under elevated CO2. Photosynthetic rates at 15°C or 35°C were also higher in elevated than in ambient C02-grown plants, when measured at their respective CO2 growth condition. Stomata of elevated C02-grown plants were less responsive to temperature as compared to ambient CO2 plants. The after effect of a heat-shock treatment (4 h at 45°C in a chamber with 80% of relative humidity and 800—1000 tmol rn2 photon flux density) on Amax was less in elevated than in ambient C02-grown plants. At the photochemical level, the negative effect of the heat-shock treatment was slightly more pronounced in ambient than in elevated CO2-grown plants. A greater tolerance to oxidative stress caused by high temperatures in elevated C02-grown plants, in comparison to ambient CO2 plants, is suggested by the increase in superoxide dismutase activity, after 1 h at 45°C, as well as its relatively high activity after 2 and 4 h of the heat shock in the elevated C02-grown plants in contrast with the decrease to residual levels of superoxide dismutase activity in ambient C02-grown plants immediately after 1 h at 45°C. The observed increase in catalase after 1 h at 45°C in both ambient and elevated C02-grown plants, can be ascribed to the higher rates of photorespiration and respiration under this high temperature.
Keywords: catalase; Elevated CO2; photosynthesis; Quercus suber L.; superoxide dismutase; Temperature

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 16390425
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Study of some characteristic Mediterranean vegetation species best suited for renaturalization of terminal-phase municipal solid waste (MSW) landfills in Puglia (Southern Italy) - De Mei, Massimiliano; Di Mauro, Mariaida (Acta Oecologica, 2006)
Natural recovery of worked-out or closed municipal solid waste (MSW) landfills is a current topic, but knowledge about the adaptability of Mediterranean vegetation species to such stressful conditions is still quite poor. Autochthonous plants were selected to withstand the stresses such as hot climate and drought typical of Mediterranean areas; this characteristic potentially allows the plants an easier, efficient adaptation. Our aim was to provide information in order to obtain an adequate quality of environmental renewal of a landfill and a reduced management cost while ensuring rehabilitation to an acceptable naturalistic state. The investigation lasted 3 years; some Mediterranean scrub native plant species were selected and monitored in their morphological (total and relative height, basal diameter, number of inter-nodes) and physiological (photosynthetic rate and water potential) activity. In order to test dependence on CO2 concentration, different meteorological parameters were also monitored. Ceratonia siliqua, Phillyrea latifolia, Olea europaea and Quercus ilex showed considerable adaptability, reacting positively to every improvement in environmental conditions, particularly those of a meteorological nature. Survival and growth was satisfactory in Hedysarum coronarium, Medicago sativa, Lotus corniculatus, Rosmarinus officinalis, Myrtus communis and Viburnum tinus. Fraxinus ornus and Acer campestre suffered stress during the summer dry period and recovered quickly when atmospheric conditions improved. A drop irrigation system to ensure a satisfactory soil moisture during summer dry periods was the fundamental element for survival
Keywords: Biogas; Carbon dioxide; Carbon dioxide concentration; climate; Gramineae; herbaceous; Landfills; Leguminosae; photosynthesis; Plant morphology; Precipitation; Scrub arboreal species; Soil; Temperature; water potential

Refining vegetation simulation models: From plant functional types to bioclimatic affinity groups of plants - Laurent, J.-M.; Bar-Hen, A.; François, L.; Ghislain, M.; Cheddadi, R. (Journal of Vegetation Science, 2004)
Question: How to refine simulations based on a global vegetation model in order to apply it to regional scale? Location: Europe from 35° N to 71° N and 25° W to 70° E. Methods: Geographical ranges of European plants were georeferenced and used with monthly mean climatic data (diurnal temperature ranges, ground frost frequencies, precipitation, relative humidity, rain frequencies, amount of sunshine hours and temperature) and growing degree days to infer climatic boundaries for 320 taxa. We performed a discriminant analysis to define their potential geographic ranges. Hierarchical clustering was computed on potential ranges. Results: Clustering provided 25 Bioclimatic Affinity Groups (BAG) of plants consisting of 13 tree, seven shrub and five herb groups. These B AGs are characterized by different geographical ranges and climatic tolerances and requirements. Conclusion: The use of monthly data instead of annual values improved the prediction of potential distribution ranges and highlighted the importance of climate seasonality for defining the plant groups with accuracy. The B AGs are detailed enough to provide finer reconstructions and simulations of the vegetation at the regional scale.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: CARAIB; Discriminant analysis; Hierarchical clusteranalysis; Moisture; pollen; Seasonality; Temperature; Vegetation distribution

Measurement and characterization of cellulase activity in sclerophyllous forest litter. - Criquet, Stéven (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.
The following values have no corresponding Zotero field: accession-num: 11997167
Keywords: Buffers; Cellulase; Cellulase: analysis; Cellulase: isolation & purification; Cellulose; Cellulose: metabolism; Endoglucanase; Extraction; Hydrogen-Ion Concentration; Isoenzyme; Isoenzymes; Isoenzymes: analysis; litter; Plant Leaves; Plant Leaves: enzymology; Quercus; Quercus: enzymology; Temperature; Trees

Short-term responses of terpene emission rates to experimental changes of PFD in Pinus halepensis and Quercus ilex in summer field conditions - Penuelas, J.; Llusia, J. (Environmental and Experimental Botany, 1999)
The diurnal relationships of monoterpene emission with PFD and photosynthetic rates were studied in the Mediterranean trees Pinus halepensis, a terpene storing species, and Quercus ilex, a non-storing species, under summer ﬁeld conditions. At morning, midday and evening, leaves were submitted to different irradiance levels by differentially shading them. Both species emitted large amounts of monoterpenes (about 20 mg g DM1 h1 ). The most emitted terpene by P. halepensis was D 3 -carene followed by b-myrcene, a-pinene and b-pinene. The most emitted terpene by Q. ilex was limonene followed by a-pinene and b-pinene. No clear correlation to temperature was found for Q. ilex emission within the diurnal range of 21–33°C, whereas P. halepensis emissions increased with the temperature. There was no consistent link between terpene emissions and PFD or photosynthetic rates for P. halepensis but there were signiﬁcant relationships for Q. ilex. However, emissions by Q. ilex became inhibited at highest PFDs and during the course of the day when net photosynthesis decreased under summer drought. The study shows that the emission rates of both species are highly variable and that during a hot Mediterranean summer day (with limited water availability) the diurnal variation of emission is not only driven by the common light and temperature dependencies. Water stress, branch-to-branch variability and other inﬂuences must explain great part of the observed variability
Keywords: a-pinene; d 3 -carene; field conditions; limonene; pfd; photosynthetic rate; Pinus halepensis; Quercus ilex; Temperature; Terpene emission

Use of the isoprene algorithm for predicting the monoterpene emission from the Mediterranean holm oak Quercus ilex L.: Performance and limits of this approach - Ciccioli, Paolo; Fabozzi, Concetta; Brancaleoni, Enzo; Cecinato, Angelo; Frattoni, Massimiliano; Loreto, Francesco; Kesselmeier, Jürgen; Schäfer, Luise; Bode, Kirsten; Torres, Liberto; Fugit, Jean-Luc (Journal of Geophysical Research: Atmospheres, 1997)
The algorithm developed by Guenther et al. [1991] to describe the organic emission of isoprene-emitting plants has been used for predicting monoterpene emission from Quercus ilex L., an evergreen oak typical of the Mediterranean basin. The dependence of monoterpene emission on photosynthetically active radiation and temperature has been verified through laboratory experiments carried out on single leaves as well as through field measurements at branch level. While the algorithm describes well monoterpene emission under stationary state conditions, it is less accurate when rapid fluctuations of light and temperature take place. Because of this, the isoprene algorithm is capable of predicting the response of Quercus ilex L. with an accuracy better than ±25% only in 65% of the environmental situations experienced by the plant. Field and laboratory observations consistently indicate that temperature oscillations can be an important source for the discrepancies between predicted and observed values as they can generate bursts of emission with values twice as high as those predicted by the algorithm. Possible causes generating these effects are analyzed and critically discussed. In spite of the observed limitations, the isoprene algorithm can successfully describe the biogenic emission from Quercus ilex L., and its use is advantageous as it greatly simplifies regional and global emission models, especially if the light dependence of monoterpene emission is proven to be a widespread phenomenon.
Keywords: Biogenic emission; isoprene algorithm; monoterpene (voyant); Quercus ilex; Temperature

Growth at elevated CO2 leads to down-regulation of photosynthesis and altered response to high temperature in Quercus suber L. seedlings - FARIA, T.; Wilkins, D.; Besford, R. T.; Vaz, M.; Pereira, J. S.; Chaves, M. M. (Journal of Experimental Botany, 1996)
The effects of growth at elevated CO2 on the response to high temperatures in terms of carbon assimilation (net photosynthesis, stomatal conductance, amount and activity of Rubisco, and concentrations of total soluble sugars and starch) and of photochemistry (for example, the efficiency of excitation energy captured by open photosystem II reaction centres) were studied in cork oak (Quercus suber L.). Plants grown in elevated CO2 (700 ppm) showed a down-regulation of photosynthesis and had lower amounts and activity of Rubisco than plants grown at ambient CO2 (350 ppm), after 14 months in the greenhouse. At that time plants were subjected to a heat-shock treatment (4 h at 45°C in a chamber with 80% relative humidity and 800–1000 µmol m−2 s−1 photon flux density). Growth in a CO2-enriched atmosphere seems to protect cork oak leaves from the short-term effects of high temperature. Elevated CO2 plants had positive net carbon uptake rates during the heat shock treatment whereas plants grown at ambient CO2 showed negative rates. Moreover, recovery was faster in high CO2-grown plants which, after 30 min at 25°C, exhibited higher net carbon uptake rates and lower decreases in photosynthetic capacity (Amax as well as in the efficiency of excitation energy captured by open photosystem II reaction centres (FvJFm than plants grown at ambient CO2. The stomata of elevated CO2 plants were also less responsive when exposed to high temperature.
10.1093/jxb/47.11.175510.1093/jxb/47.11.1755
Keywords: acclimation; Elevated CO2; photo- synthesis; Quercus suber L.; Temperature

INFLUENCIA DE LAS COBERTURAS DE ENCINAS , Quercus ilex subsp. ballota , EN LA ROTURA DE LOS PERFILES TERMICOS VERTICALES - Escudero Garcia, J. C.; Cabezas Fernández, J.; Lavado Contador, F. (CONGRESO FORESTAL ESPAÑOL - Lourizán 1.993, 1993)
Vegetation cover acts intensely on vertical temperature profiles, breaking up their structure. For the particular case of holm oak parkland (dehesas) forests systems, these will affect the vertical temperature gradient by modifying it more or less sharply as a function funtamenta1ly of the height and characteristics of the canopy, the density of trees ánd of foliage load. The study was carried in Cheles (Badajoz), and consisted in periodic measurements of the temperature variations in the profile. The results show quantitatively the influence of arboreal systems on the vertical structure of air and soil temperatures. A characterlzation is thereJore given of the thermal impact that intense pruning and destruction of holm oaks have on the vertical profIle, especially that of he soil.
The following values have no corresponding Zotero field: periodical: CONGRESO FORESTAL ESPAÑOL - Lourizán 1.993
Keywords: gradients; impact; Quercus ilex; Temperature

Mediterranean pasture dynamics: the role of germination - Espigares, T.; Peco, B. (Journal of Vegetation Science, 1993)
pastures were arranged along a gradient of sensitivity to temperature on the arrival of the first persistent rain. This sensitivity was manifested in both the total germination success of the species and the germination time profile. The different germination patterns of the species can provide competitive advantages depending on the autumn weather conditions.
Keywords: Autumn rain; Gradient; Phytotron; seed bank; Temperature; Weather fluctuation